133. ARGONAUT-III: Susceptibility of Carbapenem-resistant Klebsiellae to Cefepime-Taniborbactam. (4th December 2021) - Mack, Andrew R; Bethel, Christopher; Marshall, Steven; Patel, Robin; Patel, Robin; van Duin, David; Fowler, Vance G; Rhoads, Daniel D; Jacobs, Michael; van den Akker, Focco; Six, David A; Moeck, Greg; et al.
Abstract: Background: Klebsiellae are Gram-negative pathogens responsible for serious nosocomial and community-acquired infections. Carbapenem resistance, both intrinsic and acquired, complicates therapy. Taniborbactam (formerly VNRX-5133; Fig 1) is a bicyclic boronate β-lactamase inhibitor (BLI) that inhibits all four Ambler classes of β-lactamase enzymes, both serine- and metallo-, with the notable exception of class B IMP β-lactamases. Taniborbactam is currently undergoing phase 3 clinical trials in combination with cefepime (FEP; Fig 1) as part of the β-lactam-BLI (BL-BLI) combination FEP-taniborbactam (FTB). Figure 1. Structures of taniborbactam and cefepime. The β-lactamase inhibitor is in red and the β-lactam antibiotic is in black. Methods: We determined the activity of FTB against 200 carbapenem-resistant Klebsiellae (CRK) strains collected as part of the Antibiotic Resistance Leadership Group (ARLG) Consortium on Resistance against Carbapenems in Klebsiella (CRACKLE) study. Among these strains, 193 expressed class A KPCs, one expressed a class B NDM, and six expressed class D OXA-48 or variants. Broth microdilution minimum inhibitory concentrations (MIC)s were determined using the ThermoFisher Sensititre system with custom assay panels. American Type Culture Collection strains were used for quality control. The susceptible-dose-dependent breakpoint for FEP was provisionally used for FTB, where taniborbactam was fixed at 4 µg/mL. Results: Among the 200 Klebsiella strains tested, susceptibility for β-lactams alone ranged from 1% for ceftazidime (CAZ), 2.5% for meropenem, and 13.5% for FEP (Table 1). The addition of BLIs increased % susceptibility compared to BL alone to: 98% for CAZ-avibactam (CZA); 95.5% for MEM-vaborbactam (MVB); and 99.0% for FTB. MIC50 and MIC90 were in the susceptible and provisionally susceptible range for CZA and MVB, and in the provisionally susceptible range for FTB. Analyzing the CZA and MVB non-susceptible strains, 7 of 9 MVB non-susceptible strains and 2 of 4 CZA-resistant strains were provisionally susceptible to FTB. Table 1. MIC50 and MIC90 values (μg/mL) and percent susceptibility for Klebsiella pneumoniae strains (n=200). AMK, amikacin; CST, colistin; CAZ, ceftazidime; CZA, ceftazidime-avibactam; FEP, cefepime; FTB, cefepime-taniborbactam; MEM, meropenem; MVB, meropenem-vaborbactam; TGC, tigecycline. * The breakpoint for CST is intermediate, as no susceptible breakpoint is available. ** The susceptible-dose-dependent breakpoint for FEP alone was provisionally applied to FTB, where taniborbactam was fixed at 4 μg/mL. Breakpoints from CLSI M100, 31st ed, 2021. Conclusion: The addition of taniborbactam restored susceptibility to FEP in 99.0% of CRACKLE isolates studied, comparable to CZA and MVB. Taniborbactam also restored FEP activity against some MVB- and CZA-resistant strains. FTB may provide a promising therapy for CRK infections. Disclosures: Robin Patel, MD, 1928 Diagnostics (Consultant)BioFire Diagnostics (Grant/Research Support)ContraFect Corporation (Grant/Research Support)Curetis (Consultant)Hylomorph AG (Grant/Research Support)IDSA (Other Financial or Material Support, Editor's Stipend)Infectious Diseases Board Review Course (Other Financial or Material Support, Honoraria)Mammoth Biosciences (Consultant)NBME (Other Financial or Material Support, Honoraria)Netflix (Consultant)Next Gen Diagnostics (Consultant)PathoQuest (Consultant)PhAST (Consultant)Qvella (Consultant)Samsung (Other Financial or Material Support, Patent Royalties)Selux Diagnostics (Consultant)Shionogi & Co., Ltd. (Grant/Research Support)Specific Technologies (Consultant)TenNor Therapeutics Limited (Grant/Research Support)Torus Biosystems (Consultant)Up-to-Date (Other Financial or Material Support, Honoraria) Robin Patel, MD, BioFire (Individual(s) Involved: Self): Grant/Research Support; Contrafect (Individual(s) Involved: Self): Grant/Research Support; IDSA (Individual(s) Involved: Self): Editor's stipend; NBME, Up-to-Date and the Infectious Diseases Board Review Course (Individual(s) Involved: Self): Honoraria; Netflix (Individual(s) Involved: Self): Consultant; TenNor Therapeutics Limited (Individual(s) Involved: Self): Grant/Research Support; to Curetis, Specific Technologies, Next Gen Diagnostics, PathoQuest, Selux Diagnostics, 1928 Diagnostics, PhAST, Torus Biosystems, Mammoth Biosciences and Qvella (Individual(s) Involved: Self): Consultant David van Duin, MD, PhD, Entasis (Advisor or Review Panel member)genentech (Advisor or Review Panel member)Karius (Advisor or Review Panel member)Merck (Grant/Research Support, Advisor or Review Panel member)Pfizer (Consultant, Advisor or Review Panel member)Qpex (Advisor or Review Panel member)Shionogi (Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member)Utility (Advisor or Review Panel member) Vance G. Fowler, Jr., MD, MHS, Achaogen (Consultant)Advanced Liquid Logics (Grant/Research Support)Affinergy (Consultant, Grant/Research Support)Affinium (Consultant)Akagera (Consultant)Allergan (Grant/Research Support)Amphliphi Biosciences (Consultant)Aridis (Consultant)Armata (Consultant)Basilea (Consultant, Grant/Research Support)Bayer (Consultant)C3J (Consultant)Cerexa (Consultant, Other Financial or Material Support, Educational fees)Contrafect (Consultant, Grant/Research Support)Debiopharm (Consultant, Other Financial or Material Support, Educational fees)Destiny (Consultant)Durata (Consultant, Other Financial or Material Support, educational fees)Genentech (Consultant, Grant/Research Support)Green Cross (Other Financial or Material Support, Educational fees)Integrated Biotherapeutics (Consultant)Janssen (Consultant, Grant/Research Support)Karius (Grant/Research Support)Locus (Grant/Research Support)Medical Biosurfaces (Grant/Research Support)Medicines Co. (Consultant)MedImmune (Consultant, Grant/Research Support)Merck (Grant/Research Support)NIH (Grant/Research Support)Novadigm (Consultant)Novartis (Consultant, Grant/Research Support)Pfizer (Grant/Research Support)Regeneron (Consultant, Grant/Research Support)sepsis diagnostics (Other Financial or Material Support, Pending patent for host gene expression signature diagnostic for sepsis.)Tetraphase (Consultant)Theravance (Consultant, Grant/Research Support, Other Financial or Material Support, Educational fees)Trius (Consultant)UpToDate (Other Financial or Material Support, Royalties)Valanbio (Consultant, Other Financial or Material Support, Stock options)xBiotech (Consultant) Daniel D. Rhoads, MD, Becton, Dickinson and Company (Grant/Research Support) Michael Jacobs, MBBS, Venatorx Pharmaceuticals, Inc. (Grant/Research Support) Focco van den Akker, PhD, Venatorx Pharmaceuticals, Inc. (Grant/Research Support) David A. Six, PhD, Venatorx Pharmaceuticals, Inc. (Employee) Greg Moeck, PhD, Venatorx Pharmaceuticals, Inc. (Employee) Krisztina M. Papp-Wallace, Ph.D., Merck & Co., Inc. (Grant/Research Support)Spero Therapeutics, Inc. (Grant/Research Support)Venatorx Pharmaceuticals, Inc. (Grant/Research Support)Wockhardt Ltd. (Other Financial or Material Support, Research Collaborator) Robert A. Bonomo, MD, entasis (Research Grant or Support)Merck (Grant/Research Support)NIH (Grant/Research Support)VA Merit Award (Grant/Research Support)VenatoRx (Grant/Research Support)